Spiritualiteit in het Lucasevangelie. Verwachting en volharding - H. Welzen (Acta Theologica)
This article focuses on Luke’s expectation of the parousia. The intended readers live in the time after the destruction of Jerusalem, but before the coming of the Son of Man. The isomorfism of these events is important for the impact of the gospel to its readers. In Luke’s view Jerusalem’s rejection of Gods liberation has led to the destruction of the city. In a similar way the positive or negative response of the intended readers will determine whether they will or will not experience liberation at the coming of the Son of Man. A positive reaction is characterized by perseverance, prayer and faith. Luke’s gospel is part of a tradition initiated by the transition of the eyewitnesses to the servants of the word. In the last chapter of the gospel this transition is realized completely. The transformation of the disciples is also the transition to Acts.